PENGARUH PERENCANAAN PAJAK DAN PRINSIP KONSERVATISME AKUNTANSI TERHADAP PRAKTIK MANAJEMEN LABA ( Studi Empiris pada Perusahaan Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia Tahun 2013-2015 ) - Peri Purwanti; Ermadiani Ermadiani; Aryanto Aryanto (AKUNTABILITAS, 2016)
The purpose of this research is to analyze the influence of the Tax Planning and Principle of Accounting Conservatism to Earnings Management. Samples in this research are 10 Food and Beverage companies listed on Indonesia Stock Exchange from 2013-2015. This research used multiple linear regression analysis. The result shows that Tax Planning and Principle of Accounting Conservatism have influence on Earnings Management.